A case-control study comparing and correlating iNOS expression among various clinicopathological variants of oral leukoplakia and oral squamous cell carcinoma: A Immunohistochemistry study - Deepak N Singh; Kumar Chandan Srivastava; Aparna D Potsangbam; Deepti Shrivastava; Doddabasavaiah Basavapur Nandini; Wahengbam T Singh; Koijam S Singh (Wolters Kluwer Medknow Publications, 2020)
Background and Objective: The role of inducible nitric oxide synthase (iNOS) has been implicated in various pathological processes including oral carcinoma. Oral premalignancy being its precursor lesion is also expected to show similar pattern. This study attempts to appraise the iNOS expression in various clinicopathological stages and grades of oral leukoplakia (OL) and oral squamous cell carcinoma (OSCC). Materials and Methods: A case-control study design was adopted for this study with a total sample of 90 subjects, distributed equally into the three study groups, namely controls, OL, and OSCC. Clinical staging and histopathological grading for both the case groups were performed. Representative tissue samples from all groups were obtained and studied for iNOS expression using immunohistochemistry (IHC). Data were presented in mean and percentages accordingly. Inferential analysis was performed using Kruskal-Wallis test, Mann-Whitney test, and Spearman rank correlation test. Results: Significant (P < 0.001) difference was observed among the groups, where 83.3% of OSCC and 73.3% of OL epithelial cells showed iNOS expression. The normal cells did not show up any expression. The expression was found to rise with the progressing clinical stages of OL (P < 0.05) and OSCC (P < 0.01). Similar pattern was observed with respect to advancing dysplasia in OL (P < 0.01) and cell differentiation in OSCC (P < 0.01). Significant positive correlation was found in clinicopathological categories of OL and OSCC. Considering the risk assessment, iNOS staining was found to be significantly raised in advanced cases of OSCC (P < 0.01) and high-risk cases of OL (P < 0.01). Conclusion: Increased expression of iNOS can be an early diagnostic marker in OL and as prognostic marker in OSCC.